Light and Luminaries: A Study of Genesis 1:3–5 and 14–19. - Bediako, Daniel Kwame (Journal of Biblical Literature, 2025)
The question of the relationship between אור ("light") and מארת ("luminaries") in Gen 1 has received differing answers, with some interpretations moving further away from the text as it stands. In this study, I reexamine verses 3–5 and verses 14–19 from a linguistic perspective and conclude that the biblical writer of Gen 1 assumes a distinction between אור and מארת and places the creation of מארת on the fourth day.